Does Consumer Irrationality Trump Consumer Sovereignty? - Waldfogel, Joel (The Review of Economics and Statistics, 2005)
Scholars working on the border of economics and psychology have documented many contexts in which individual decision-making is unreliable and might be improved by paternalistic interventions. Against this mounting body of negative evidence, economists' default belief in consumer sovereignty has been motivated primarily by theory rather than evidence. The goal of the present study is to see whether there is direct evidence supporting economists' faith in consumer sovereignty in a simple context. We address this question by presenting direct evidence that consumers' own purchases generate between 10% and 18% more value, per dollar spent, than items received as gifts.